2017
DOI: 10.18203/2320-6012.ijrms20174917
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of sigma metrics results of serum glucose and lipid profile tested by automated chemistry analyzer in medical city hospitals in Iraq

Abstract: Background: A major target of quality assurance is the minimization of error rates in order to enhance patient safety, six sigma or sigma metrics were used to assess the analytical quality of automated clinical chemistry, six sigma metrics is used in combination with total allowable error, method imprecision and bias. The goal is to attain the highest possible sigma scale within the acceptable limits of total allowable error. For assessment of sigma metrics results of serum glucose and lipid profile and verifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
1
1
0
Order By: Relevance
“…Our study correlates well with similar studies from Asia and Middle East. In these studies, urea was also found to be <3 sigma while ALKP was found to have >6 sigma [10][11][12][13][14][15][16][17][18] (Table 5) A recent study in India by Vijatha et al, shows excellent correlation with the present study. 18 Our study also showed good correlation with a similar study by Nanda et al where >6 sigma was observed for uric acid, total bilirubin, SGOT, SGPT, TG and ALP.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our study correlates well with similar studies from Asia and Middle East. In these studies, urea was also found to be <3 sigma while ALKP was found to have >6 sigma [10][11][12][13][14][15][16][17][18] (Table 5) A recent study in India by Vijatha et al, shows excellent correlation with the present study. 18 Our study also showed good correlation with a similar study by Nanda et al where >6 sigma was observed for uric acid, total bilirubin, SGOT, SGPT, TG and ALP.…”
Section: Discussionsupporting
confidence: 83%
“…9 El Sharkawy et al, in 2018, proposed a harmonized protocol for sigma calculation and highlighted the importance of selecting TEa goals. 11 Sigma metric changes according to the chosen TEa goal and each lab should have a standardized criterion for selecting the same, as under-or overestimation of sigma metric will affect patient results. The world is yet to reach a consensus regarding the most ideal quality goal to be used, and herein lies the biggest challenge of using sigma metrics.…”
Section: Discussionmentioning
confidence: 99%